Short-term efficacy and safety of a lower dose of polyethylene glycol recombinant human growth hormone in children with growth hormone deficiency: A randomized, dose-comparison study - Jiang, Zhouhong; Chen, Xuefeng; Dong, Guanping; Lou, Yin; Zhang, Jianping; Cheng, Xinran; Pan, Jiayan; Liao, Wei; Wu, Jinzhun; Huang, Xiaodong; Jin, Xianjiang; Liu, Deyun; et al. (Frontiers in Pharmacology, 2022)
Objective: Polyethylene glycol recombinant human growth hormone (PEG-rhGH, Jintrolong®) is the first long-acting rhGH preparation that is approved to treat children with growth hormone deficiency (GHD) in China. Clinical experience with individualized dosing of PEG-rhGH is scarce. Owing to the high cost of treatment, the present study amid to evaluate the efficacy and safety of a lower dose of PEG-rhGH. Methods: A multicenter, randomized, open-label, dose-comparison clinical study was conducted to compare the improvements in the height standard deviation score (Ht SDS), height velocity (HV), insulin-like growth factor-1 (IGF-1) SDS, and safety profiles of children with GHD who are treated with 0.2 mg/kg/week of PEG-rhGH dose or 0.14 mg/kg/week for 26 weeks. Results: Ht SDS, HV, and IGF-1 SDS increased significantly after PEG-rhGH treatment in the two dose groups (p<0.05). The improvements of Ht SDS, HV, and IGF-1 SDS were more significant in the high-dose group than in the low-dose group (p<0.05). HV increment in low-dose group was non-inferior to that in the high-dose group. The incidences of adverse events were comparable between the two groups. Conclusion: PEG-rhGH at the dose of 0.14mg/kg/week was effective and safe for children with GHD. The efficacy of 0.14mg/kg/week was considered non-inferior in HV to 0.2 mg/kg/week.